Nanomedicine-Based Ophthalmic Drug Delivery Systems for the Treatment of Ocular Diseases - Lin X; Zhou Y; Lv K; Wu W; Chen C (International Journal of Nanomedicine)
Xin Lin,1– 3,* Yali Zhou,3– 5,* Kangjia Lv,3– 5,* Wenjie Wu,1,2 Chong Chen3– 5 1Shengli Clinical Medical College of Fujian Medical University, Fujian Medical University, Fuzhou, Fujian Province, People’s Republic of China; 2Department of Ophthalmology, Fujian Provincial Hospital, Fuzhou University Affiliated Provincial Hospital, Fuzhou, Fujian Province, People’s Republic of China; 3Shanghai Key Laboratory of Ocular Fundus Diseases, Shanghai General Hospital, Shanghai, People’s Republic of China; 4Department of Ophthalmology, Shanghai General Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 5National Clinical Research Center for Eye Diseases, Shanghai General Hospital, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wenjie Wu, Department of Ophthalmology, Fujian Provincial Hospital, Fuzhou University Affiliated Provincial Hospital, 134 East Street, Fuzhou, Fujian Province, 350000, People’s Republic of China, Tel/Fax +86 8821 7110, Email wenjie_wu@foxmail.com Chong Chen, Department of Ophthalmology, Shanghai General Hospital, Shanghai Jiao Tong University School of Medicine, 100 Haining Road, Shanghai, 200080, People’s Republic of China, Tel +8615802167095, Email chong.chen1@shgh.cnAbstract: Ocular diseases affect over 2.2 billion people globally, imposing a significant socioeconomic burden, with annual productivity losses estimated at US$411 billion. Conventional drug delivery methods—topical, local injection, and systemic administration—face challenges such as low bioavailability (< 5%), rapid clearance, and physiological barriers like the cornea and blood-retinal barrier (BRB). Nanomedicine offers promising solutions by enhancing drug bioavailability, prolonging release, and enabling targeted delivery. This review explores nanomedicine-based ophthalmic drug delivery systems, including organic nanomaterials (eg, liposomes, polymer micelles, dendrimers), inorganic nanomaterials (eg, metal nanoparticles, quantum dots), and biological components (eg, exosomes). These systems improve drug penetration, reduce administration frequency, and minimize toxicity, addressing conditions like dry eye disease, keratitis, glaucoma, uveitis, age-related macular degeneration (AMD), diabetic retinopathy (DR), and retinal vascular occlusion (RVO). For instance, Ocular Therapeutix (OTX)-TP, a sustained-release intracanalicular implant combining poly (ethylene glycol)-based hydrogel with travoprost-loaded poly (lactic acid) microspheres, has shown therapeutic efficacy lasting up to three months in the management of glaucoma and ocular hypertension in Phase III clinical trial. Additionally, a liposomal formulation of verteporfin, approved for the treatment of neovascular AMD, administered intravenously and activated by laser photodynamic therapy, demonstrates a durable response, with a marked reduction in treatment frequency from an average of 3.5 sessions in the first year to only 0.1 by the fifth year post-diagnosis. Despite these advantages, challenges such as manufacturing costs, potential toxicity, and limited clinical translation persist. Future advancements in nanomedicine hold potential for personalized, non-invasive ocular therapies, revolutionizing ophthalmology.Keywords: nanomedicine, ophthalmic drug delivery, ocular diseases, physiological barriers, targeted delivery